Analisis Faktor Risiko yang Mempengaruhi Kejadian Obesitas pada Remaja: Studi Literatur - Karimah, Amani Shofi; Niarto, Zaskia Reihan Amanda; Lesmana, Dinda Annisa Putri; Faris, Ahlam; Herbawani, Chahya Kharin (Jurnal Keperawatan Florence Nightingale, 2025)
The prevalence of obesity in adolescents has significantly increased from 8% in 1990 to 20% in 2022. The World Health Organization (WHO) reports that more than 390 million children and adolescents aged 5 to 19 years are affected by obesity. This study aims to identify risk factors contributing to obesity in adolescents and is expected to help them avoid behaviors that could potentially lead to obesity. This literature review study utilizes the PRISMA guidelines and databases such as Google Scholar, Garuda, MDPI, PubMed, and ScienceDirect. Articles were searched using keywords in both Indonesian and English, such as "risk factors for adolescent obesity," "risk factor," "obesity," and "adolescent," for publications from 2021 to 2024, in accordance with predefined inclusion and exclusion criteria. Based on the review of 10 articles, it was found that risk factors influencing obesity in adolescents include genetic factors, gender, physical activity, parental income, eating habits, knowledge, and stress levels. Physical activity is the dominant factor influencing obesity in adolescents. Therefore, optimal interventions are needed to prevent obesity in adolescents, including programs to increase physical activity and family support to promote healthy eating habits.